Treatment of Ankyloglossia: A Review - Alessandro Frezza; Fatima Ezeddine; Andrea Zuccon; Antonio Gracco; Giovanni Bruno; Alberto De Stefani (MDPI AG, 2023)
Aim: The aim of this narrative review is to analyze and compare the current scientific evidence regarding the diagnosis and treatment of hypertrophic lingual frenulum in preschool and school-age children. The treatments considered in this review are traditional surgical therapy, laser-assisted surgical therapy, and functional rehabilitation therapy. Materials and methods: A comprehensive literature review was conducted using the PubMed and PubMed Central search engines, considering articles published in the English language between 1 January 2000 and 30 June 2022. The bibliographic search was performed using the following keywords as search strings: "lingual", "frenulectomy", "frenulotomy", "frenulum", "ankyloglossia", and "laser." Results: A total of 14 articles were included in this review, including four prospective observational studies, one case-control study, three cross-sectional studies, four retrospective studies, and one randomized controlled trial. The data extracted from each article are summarized in a table. Conclusions: In the literature, there are still limited studies regarding the treatment of hypertrophic frenulum. No common indications for the treatment of ankyloglossia and universally used classification for lingual frenulum were found. Currently, clinicians prefer the use of a diode laser for treatment. This method offers several advantages over the use of a scalpel blade. Many studies agree on the usefulness of providing patients with myofunctional rehabilitation to improve lingual mobility, both prior to surgical therapy and in the postoperative period.